2019
DOI: 10.1111/cdoe.12501
|View full text |Cite
|
Sign up to set email alerts
|

Oral and dental health and health care for Māori with type 2 diabetes: A qualitative study

Abstract: Objectives Type 2 diabetes mellitus (T2DM) and periodontal disease are two highly prevalent, directly and independently associated long‐term conditions that disproportionately impact Indigenous Māori in New Zealand (NZ). Although poorly understood, a number of social and biological mechanisms connect these conditions. This qualitative study explored experiences of T2DM and oral and dental (hereafter oral/dental) health; access to oral/dental health care; whether participants’ experiences supported or challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Older adults suffering from morbidities like diabetes and hypertension were found to have more tooth related problems compared to those not reporting the disease. Studies exploring the association of diabetes with dental care emphasized oral health assessment (27,41). A study by Kudpi et al,(42) on 211 older adult patients revealed that most of the patients with tooth loss were diabetic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults suffering from morbidities like diabetes and hypertension were found to have more tooth related problems compared to those not reporting the disease. Studies exploring the association of diabetes with dental care emphasized oral health assessment (27,41). A study by Kudpi et al,(42) on 211 older adult patients revealed that most of the patients with tooth loss were diabetic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly suffering from morbidities like diabetes and hypertension were found to be having more dental problems compared to those not reporting the disease. Studies exploring the association of diabetes with dental care emphasized oral health assessment (26,40). A study by Kudpi et al, (44) on 211 elderly patients revealed that most of the patients with tooth loss were diabetic and hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between periodontitis severity and future increases in medical care costs was found among older Japanese (198). Adults with DM consistently have fewer regular dental checkups than their non-DM peers (22,(199)(200)(201)(202)(203)(204)(205)(206)(207)(208) with between 25 and 60% having had a dental visit the last year. Nonetheless, patients with DM who do receive dental care experience incremental higher costs for more complex treatment and restoration of missing teeth rather than preventive visits (203).…”
Section: Dental Treatment Reduces Healthcare-related Costs In Diabetesmentioning
confidence: 97%